Introduction to R for Data Analysis (Part A) - Voutsa, Maria C. (My University, 2026)
Introduction to R for Data Analysis aims to introduce you to the world of R, a powerful programming language for statistical analysis. R is popular due to its free nature, wide availability, online help, and utility compared to other programming languages. The course is divided into two sub-sections: The first section introduces R Studio, exploring the basic structure of R and its use, including working with structures, data types, and libraries. The second section focuses on data analysis, including statistical methods and data visualization.